Pengenalan Masa Puberitas Pada Peserta Didik Sekolah Dasar - Nurdin, Nurdin; Yusal, Muh. Sri; Nur, Surahman; Rasjid, Yusniar; Rais, Zulkifli (Panrannuangku Jurnal Pengabdian Masyarakat, 2023)
Counseling on menarche and puberty for students of SD Negeri 1 Mattoanging Makassar. This activity aims to: 1. Conduct counseling about the period of marache and puberty, as well as the effect of nutritional intake on menstruation for students as material for additional knowledge for students when facing metabolic changes in their bodies. 2. Changes that occur after experiencing marache or menstruation. 3. How to overcome the problems faced by the body when menstruation occurs.